101 Reasons for a Citizen's Income : Arguments for Giving Everyone Some Money - Torry, Malcolm (Book collections on Project MUSE., 2015)
101 Reasons for a Citizen's Income offers a short, accessible introduction to the debate on a Citizen's Income, showing how a universal, unconditional income for every citizen would solve problems facing the UK's benefits system, tackle poverty, and improve social cohesion and economic efficiency. For anyone new to the subject, or who wants to introduce friends, colleagues or relatives to the idea, 101 Reasons for a Citizen's Income is the book to open up debate around the topic. Drawing on arguments detailed in Money for everyone (Policy Press, 2013), it offers a convincing case for a Citizen's Income and a much needed resource for all interested in the future of welfarein the UK.